Ambient air pollution exposure and risk and progression of interstitial lung abnormalities: the Framingham Heart Study. Issue 11 (7th August 2019) - Rice, Mary B; Li, Wenyuan; Schwartz, Joel; Di, Qian; Kloog, Itai; Koutrakis, Petros; Gold, Diane R; Hallowell, Robert W; Zhang, Chunyi; O'Connor, George; Washko, George R; Hunninghake, Gary M; et al.
Abstract : Background: Ambient air pollution accelerates lung function decline among adults, however, there are limited data about its role in the development and progression of early stages of interstitial lung disease. Aims: To evaluate associations of long-term exposure to traffic and ambient pollutants with odds of interstitial lung abnormalities (ILA) and progression of ILA on repeated imaging. Methods: We ascertained ILA on chest CT obtained from 2618 Framingham participants from 2008 to 2011. Among 1846 participants who also completed a cardiac CT from 2002 to 2005, we determined interval ILA progression. We assigned distance from home address to major roadway, and the 5-year average of fine particulate matter (PM2.5 ), elemental carbon (EC, a traffic-related PM2.5 constituent) and ozone using spatio-temporal prediction models. Logistic regression models were adjusted for age, sex, body mass index, smoking status, packyears of smoking, household tobacco exposure, neighbourhood household value, primary occupation, cohort and date. Results: Among 2618 participants with a chest CT, 176 (6.7%) had ILA, 1361 (52.0%) had no ILA, and the remainder were indeterminate. Among 1846 with a preceding cardiac CT, 118 (6.4%) had ILA with interval progression. In adjusted logistic regression models, an IQR difference in 5-year EC exposure of 0.14 µg/m 3 was associated with a 1.27 (95% CI 1.04 to 1.55) times greater odds of ILA, and a 1.33 (95% CI 1.00 to 1.76) times greater odds of ILA progression. PM2.5 and O3 were not associated with ILA or ILA progression. Conclusions: Exposure to EC may increase risk of progressive ILA, however, associations with other measures of ambient pollution were inconclusive.